Development of Interactive Warehouse Operational Visualization - Mohamad Khairi Hassan; Mohd Hazri Mohd Rusli; Noor Azlina Mohd Salleh; Suzilawati M. Kayat; Joshua Goh Wen-Hann (International Journal of Integrated Engineering, 2024)
The digitalization era forces organizations to leave the conventional and manual approach of record updating for a rapid and real time data management system. This study analyzes the development of interactive process visualization from operational data, which can provide sufficient information for the user to understand current operational status. Approaches to the study include interviews to understand the current process, determining the visualization item needed and developing an interactive dashboard for visualization by using Google Data Studio @ Looker Studio. The findings revealed that an interactive operational dashboard is able to be initiated from the warehouse operation data which helps the process owner understand the operational status clearly. This study was limited to the receiving, storage and outgoing of warehouse activities that are able to create interactive information centers for the process owner to understand the warehouse operation status in real time and provide sufficient data for rapid decision and action. With a simple, low cost and practical visualization system, it will benefit society, especially the Small Medium Enterprise (SME) in moving toward digitization and digitalization towards the digital transformation of a smart factory in the Fourth Industrial Revolution (4IR).